Armazenamento de maçã 'granny smith' em atmosfera controlada dinâmica monitorada pelo quociente respiratório - Santos, Luana Ferreira dos (2016)
The most widely way used to store apples is the controlled atmosphere (CA), were the oxygen is reduced, but this is far above the lower oxygen limit (LOL) tolerated by the fruit. The use of technologies that allow the monitoring of oxygen levels at least tolerated by the fruit can help maintain quality and reduce the incidence and of physiological disorders and postharvest diseases. The dynamic controlled atmosphere (DCA) is one of these technologies, which change the O2 throughout the storage period according to the fruit metabolism. The objective of this study was to evaluate effect of DCA storage monitored by the respiratory quotient (RQ) and chlorophyll fluorescence (CF), as well as their interaction with the application of 1-methylcyclopropene (1-MCP) on the physicochemical quality and physiological disorders, especially superficial scald of 'Granny Smith' apple. The following storage conditions were evaluated: a) Conventional CA with 1.5 kPa O2 plus 1.0 kPa CO2; b) DCA-RQ 1.3; c) DCA - RQ 1.5; d) DCA - RQ 1.7; e) DCA-CF (HarvestWatchTM DCA). The CO2 partial pressure was maintained at 1.2 kPa and the temperature at 1.5 °C in all treatments. After 9 months of storage, at the fruits removal from the storage chamber, evaluations were performed for superficial scald incidence and severity, decay and healthy fruits incidence. The other evaluations were performed after a 7 days period of shelf life at 20 ° C in. Fruits stored under DCA had lower ethylene production and respiration as compared to fruits stored in conventional CA, because of the lower 1-acid-aminocyclopropane-1-carboxylic enzyme activity by apples stored in DCA-RQ 1.5 and 1.7. The storage of apples in DCA-RQ 1.5 or 1.7 resulted in low superficial scald incidence. Under these conditions the application of 1-MCP had no benefit in reducing this disorder, suggesting that their application may be needless, but it is efficient when the fruits are stored in conventional CA and DCA-CF. In fruits DCA-RQ 1.7 storage occurred most volatile production associated with fermentative metabolism, but without decline of the fruit quality. Apples stored in DCA-RQ 1.7 kept greener color as compared to fruit stored in conventional CA due to the higher concentration of total chlorophyll. The firmness of the fruit stored in DCA-RQ fruit was higher as compared to the ones stored in CA, regardless of the application of 1-MCP. Under DCA-CF, application of 1-MCP has been shown not to be beneficial for maintaining the quality of the 'Granny Smith', as it provided the highest occurrence of decay. The storage in DCA provided higher number of healthy fruits as compared to the ones stored in CA.